Measuring economic policy uncertainty in Turkey - (:unkn) unknown (Inderscience Publishers, 2021)
The purpose of this paper is to construct a monthly news-based economic policy uncertainty index for Turkey. We used the method proposed by Baker et al. (2016a) to construct the news-based index for the period from February 2000 to December 2018. We used the digital archives of five Turkish newspapers to obtain data. The results show that the Turkish EPU index is affected by both domestic and foreign events. It rises mainly with national elections, national political uncertainties, other uncertainties related to US and Turkish central banks, the failed coup attempt in Turkey, the September 11 terror attacks, and the US presidential elections. The results are in line with the expectations from emerging economies, where political instability is high. The implications of this research for emerging economies are that governments should strengthen constitutions and institutions, and that policy makers should implement economic policies that decrease country risk. Copyright © 2021 Inderscience Enterprises Ltd.
Keywords: Economic policy; Elections; Emerging economies; News-based index; Political uncertainty; Turkey; Uncertainty